2019
DOI: 10.1002/jat.3843
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale zerovalent iron particles induce differential cytotoxicity, genotoxicity, oxidative stress and hemolytic responses in human lymphocytes and erythrocytes in vitro

Abstract: The growing usage of nanoscale zerovalent iron particles (nZVI) in the remediation of soil, ground/surface water has elicited large‐scale environmental release triggering human exposure. The size of nanomaterials is a key regulator of toxicity. However, the effect of a variable size of nZVI on genotoxicity is unexplored in human cells. To the best of our knowledge, in this study, the cytotoxic, genotoxic and hemolytic potential of nZVI‐1 (15 nm) and nZVI‐2 (50 nm) at concentrations of 5, 10 and 20 μg/mL was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…PM 10, and especially PM 2.5, are considered the most harmful to human health [ 15 , 17 , 18 , 19 , 20 , 21 , 22 ]. They can penetrate the lower respiratory tract and translocate from the lung to the bloodstream, which may affect the functions of blood erythrocytes, platelets, and leukocytes [ 23 , 24 , 25 , 26 ]. Moreover, it was shown that ambient PM might contribute to the initiation and development, among others, of atherosclerosis (AS) [ 27 ], rheumatoid arthritis (RA) [ 3 ], and multiple sclerosis (MS) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…PM 10, and especially PM 2.5, are considered the most harmful to human health [ 15 , 17 , 18 , 19 , 20 , 21 , 22 ]. They can penetrate the lower respiratory tract and translocate from the lung to the bloodstream, which may affect the functions of blood erythrocytes, platelets, and leukocytes [ 23 , 24 , 25 , 26 ]. Moreover, it was shown that ambient PM might contribute to the initiation and development, among others, of atherosclerosis (AS) [ 27 ], rheumatoid arthritis (RA) [ 3 ], and multiple sclerosis (MS) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%